The Impact of Reflective Self-Assessment Journals on Enhancing Metacognitive in Speaking Classes - Tis’ah Mukarramah Khaerunnisa; La Sunra; Muh. Tahir (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to investigate how the use of reflective self-assessment journals influences the development of students' metacognitive awareness in learning English as a Foreign Language (EFL), particularly in speaking skills. This study used a qualitative approach with a classroom-based research design involving eleventh-grade students at a high school in Indonesia. Data were collected through classroom observations, students' reflective journals written in two meetings, and in-depth interviews with eight students. The data were analyzed using thematic analysis through the stages of data reduction, coding, grouping themes, and interpreting patterns of students' metacognitive awareness development based on the data sources obtained. The results of this study indicate that consistent use of reflective journals encourages the development of students' metacognitive awareness, moving from basic awareness to more complex metacognitive regulation. Students are not only able to recognize their errors and thought processes, but also begin to plan speaking strategies, monitor performance, and conduct more critical self-evaluations. These findings indicate that reflective journals serve as an effective tool for developing self-regulated learning and enhancing students' reflective abilities in English speaking. This research contributes to strengthening metacognitive-based EFL learning practices and developing more independent speaking skills.